2012
DOI: 10.1097/dcr.0b013e3182405c61
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Neuromodulation Therapy

Abstract: Sacral neuromodulation appears to be a promising new treatment option in adolescents with refractory functional constipation not responding to intensive conservative therapy. Larger randomized studies with long-term follow-up are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(11 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…SNS was a validated treatment option for urinary voiding dysfunction (31) and fecal incontinence in humans (52). Although a large number of studies have been published to investigate the therapeutic potential of SNS for constipation, most of those studies were flawed in methodologies and/or designs, such as being uncontrolled (21,25,26,34,46), retrospective (39,56), or very much underpowered (29). Although a few studies suggested a therapeutic effect of SNS on constipation, two recent randomized, controlled studies by Dinning et 61) indicated that SNS did not improve symptoms in patients with constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNS was a validated treatment option for urinary voiding dysfunction (31) and fecal incontinence in humans (52). Although a large number of studies have been published to investigate the therapeutic potential of SNS for constipation, most of those studies were flawed in methodologies and/or designs, such as being uncontrolled (21,25,26,34,46), retrospective (39,56), or very much underpowered (29). Although a few studies suggested a therapeutic effect of SNS on constipation, two recent randomized, controlled studies by Dinning et 61) indicated that SNS did not improve symptoms in patients with constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that SNS shows promise in treating idiopathic constipation (25,39,46,56). However, a number of recent studies have failed to establish the efficacy of SNS for constipation (15,21,34,42,61).…”
Section: Introductionmentioning
confidence: 99%
“…For fecal incontinence, SNM appeared to be cost-effective [ 10 , 23 ]. For constipation, these analyses have not been performed yet.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, studies of SNM for functional bowel complaints showed a positive effect on idiopathic slow and normal transit constipation resistant to conservative treatment [ 9 ]. Our preliminary data suggest that SNM may also be beneficial in young patients aged 10–20 years with refractory constipation [ 10 ]. It is unknown, however, whether relief of symptoms is sustained.…”
Section: Introductionmentioning
confidence: 99%
“… 18 In addition, sacral neuromodulation therapy has been successfully applied in adolescents with refractory functional constipation. 19 Although satisfactory outcomes regarding function have been reported in the long-term follow-up of these studies, the incidence of complications is still unknown. The use of subtotal colectomy combined with the modified Duhamel procedure, named the Jinling procedure, has been reported for the treatment of adult Hirschsprung disease, and this procedure is effective in improving the constipation scale, bowel function score, and GQL index.…”
Section: Discussionmentioning
confidence: 99%